Mitochondrial oxidative stress by Lon-PYCR1 maintains an immunosuppressive tumor microenvironment that promotes cancer progression and metastasis - Kuo, Cheng-Liang; Chou, Han-Yu; Chiu, Yi-Chieh; Cheng, An Ning; Fan, Chi-Chen; Chang, Yu-Ning; Chen, Chung-Hsing; Jiang, Shih Sheng; Chen, Nien-Jung; Lee, Alan Yueh-Luen (Cancer letters, 2020)
Mitochondrial Lon is a chaperone protein whose upregulation increases the production of mitochondrial reactive oxygen species (ROS). However, there is a lack of information in detail on how mitochondrial Lon regulates cancer metastasis through ROS production in the tumor microenvironment (TME). Our results show that elevated Lon promotes epithelial-mesenchymal transition (EMT) via ROS-dependent p38 and NF-κB-signaling. We further identified pyrroline-5-carboxylate reductase 1 (PYCR1) as a client of chaperone Lon, which induces mitochondrial ROS and EMT by Lon. Mitochondrial Lon induces ROS-dependent production of inflammatory cytokines, such as TGF-β, IL-6, IL-13, and VEGF-A, which consequently activates EMT, angiogenesis, and M2 macrophage polarization. In addition, Lon expression is induced upon the activation and M2 polarization of macrophages, which further promotes M2 macrophages to enhance the immunosuppressive microenvironment and metastatic behaviors in the TME. This raises the possibility that manipulation of the mitochondrial redox balance in the TME may serve as a therapeutic strategy to improve T cell function in cancer immunotherapy. •Mitochondrial Lon interacts with mitochondrial matrix enzyme PYCR1 to induce reactive oxygen species (ROS) production.•The inflammatory cytokines by Lon-ROS are released from cancer into the tumor microenvironment (TME) via p38-NF-κB signaling.•The chronic inflammation by Lon promotes cancer metastasis, vascular angiogenesis, and M2 macrophages polarization in the TME.•TGF-β, IL-6, IL-13, and VEGF-A induced by mitochondrial Lon promote M2 macrophage polarization in an autocrine manner.•Mitochondrial ROS stress by Lon promotes malignancies by changing the cytokine equilibrium into an immunosuppressive TME.